PIP2, An Auxin Induced Plant Peptide Hormone Regulates Root and Hypocotyl Elongation in Arabidopsis - Hussain, Saddam; Wang, Wei; Ahmed, Sajjad; Wang, Xutong; Adnan,; Cheng, Yuxin; Wang, Chen; Wang, Yating; Zhang, Na; Tian, Hainan; Chen, Siyu; Hu, Xiaojun; et al. (Frontiers in Plant Science, 2021)
Auxin is one of the traditional plant hormones, whereas peptide hormones are peptides with hormone activities. Both auxin and plant peptide hormones regulate multiple aspects of plant growth and development, and there are cross-talks between auxin and plant peptide hormones. PAMP-INDUCED SECRETED PEPTIDES (PIPs) and PIP-LIKEs (PIPLs) are a new family of plant peptide hormone, and PIPL3/TOLS2 (TARGET OF LBD SIXTEEN 2) has been shown to regulate lateral root formation in Arabidopsis. We report here the identification of PIP2 as an auxin response gene, and we found it plays a role in regulating root and hypocotyl development in Arabidopsis. By using quantitative RT-PCR, we found that the expression of PIP2 but not PIP1 and PIP3 was induced by auxin, and auxin induced expression of PIP2 was reduced in nph4-1 and arf19-4, the lost-of-function mutants of ARF7 (Auxin Response Factor 7) and ARF19, respectively. By generating and characterizing overexpressing transgenic lines and gene edited mutants for PIP2, we found root length in the PIP2 overexpression plant seedlings was slightly shorter when compared with that in the Col wild type plants, but root length of the pip2 mutant seedlings remained largely unchanged. For comparison, we also generated overexpressing transgenic lines and gene edited mutants for PIP3, as well as pip2 pip3 double mutants. Surprisingly, we found that root length in the PIP3 overexpression plant seedlings is shorter than of the PIP2 overexpression plant seedlings, and the pip3 mutant seedlings also produced short roots. However, root length in the pip2 pip3 double mutant seedlings is largely similar to that in the pip3 single mutant seedlings. On the other hand, hypocotyl elongation assays indicate that only the 35S:PIP2 transgenic plant seedlings produced longer hypocotyls when compared with the Col Wild type seedlings. Further analysis indicates that PIP2 promotes cell division as well as cell elongation in hypocotyls. Taken together, our results suggest that PIP2 is an auxin response gene, and PIP2 plays a role in regulating root and hypocotyl elongation in Arabidopsis likely via regulating cell division and cell elongation.